2022
DOI: 10.1029/2021ja030109
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐Hybrid Wave Structures and Interactions With Electrons Observed in Magnetotail Reconnection Diffusion Regions

Abstract: We investigate waves close to the lower‐hybrid frequency in 12 magnetotail reconnection electron diffusion region (EDR) events with guide field levels of near‐zero to 30%. In about half of the events, the wave vector has a small component along the current sheet normal, consistent with known lower‐hybrid drift wave properties, but the perpendicular magnetic field fluctuations can be comparable or greater than the parallel component, a feature unique to the waves inside and adjacent to EDRs. Another new wave pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…In the magnetotail, reconnection is generally symmetric and antiparallel (Eastwood et al 2010a). Meanwhile, an increasing number of reconnection events with the guide field were also detected in the magnetotail (Chen et al 2021;Tang et al 2022;Wang et al 2022).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In the magnetotail, reconnection is generally symmetric and antiparallel (Eastwood et al 2010a). Meanwhile, an increasing number of reconnection events with the guide field were also detected in the magnetotail (Chen et al 2021;Tang et al 2022;Wang et al 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Magnetic reconnection, responsible for many explosive energy release processes in laboratory and astrophysical plasmas (Chen & Shibata 2000;Ji et al 2004;Angelopoulos et al 2008;Fu et al 2013;Cao et al 2013;, efficiently converts magnetic energy into plasma energy as magnetic field lines break and reconnect (Birn et al 2001;Yamada et al 2010;Fu et al 2019aFu et al , 2019bFujimoto & Cao 2021). In the terrestrial magnetosphere, it is often observed in the magnetotail (e.g., Fu et al 2017;Wang et al 2022), at the magnetopause (e.g., Fuselier et al 2017;Cao et al 2017;Graham et al 2017;Webster et al 2018;Dong et al 2021), in the magnetosheath (e.g., Phan et al 2018;Stawarz et al 2019), and in the transition region of bow shocks (Chen et al 2019b;Gingell et al 2020). At the magnetopause, reconnection is generally asymmetric and not antiparallel (Peng et al 2017;Webster et al 2018), where plasma density, plasma temperature, and magnetic field magnitude are different on the two sides of the reconnection current sheet, and the guide field exists.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations